ANALISIS YURIDIS PUTUSAN BEBAS TERDAKWA ANGGOTA POLRI DALAM PERKARA TERTEMBAKNYA WARGA SIPIL DI MESUJI LAMPUNG - Seregig, I Ketut (Jurnal Media Hukum, 2018)
The Free Verdict handed down by the Appellate Court of the Tanjungkarang High Court is a judgment that has fulfilled the sense of justice for the defendant AKP WH as a member of the Police, because the Panel of Judges has shown the authority of this law in the eyes of the public in general and gives appreciation to the Indonesian Police measures in securing the showÂ  anarchist feelings that people do. However, the justification justifying the decision of the Tanjungkarang High Court ofÂ  Appeals Court is the issue that needs to be investigated to determine what is considered by the Panel of Justices so that in its decision to free the Defendant AKP WH from all charges.The conclusion of the research that has been done is that the free judgment handed down by the Appeals Judge to the defendant is based on several considerations that are used as justification reasons, among others; the defendant has performed his duties in accordance with the procedures laid down in the applicable law and the use of firearms to disperse anarchist masses and no longer any party to the act of the defendant, material or moral, as all parties have agreed to make peace. Reviewing the facts presented in the appeals court by the Appeals Panel is used as the Rejection and Forgiveness Reason because there is no longer any legal provisions violated by the defendant AKP WH, the Panel of Judges frees the defendant from all charges